The Effects of Lipoic Acid on Yolk Nutrient Utilization, Energy Metabolism, and Redox Balance over Time in Artemia sp. - Juan Rafael Buitrago Ramírez; Robson Matheus Marreiro Gomes; Alan Carvalho de Sousa Araujo; Sonia Astrid Muñoz Buitrago; Jean Piraine Souza; José María Monserrat (Antioxidants, 2023)
Lipoic acid (LA) is a mitochondrial coenzyme that, depending on the concentration and exposure time, can behave as an antioxidant or pro-oxidant agent and has a proven ability to modulate metabolism by promoting lipid and glucose oxidation for energy production. To assess the effects of LA on energy metabolism and redox balance over time, Artemia sp. nauplii was used as an animal model. The administered concentrations of the antioxidant were 0.05, 0.1, 0.5, 1.0, 5.0, and 10.0 µM. Therefore, possible differences in protein, triglyceride, glucose, and lactate concentrations in the artemia samples and total ammoniacal nitrogen (TAN) in the culture water were evaluated. We also measured the effects of LA on in vivo activity of the electron transport system (ETS), antioxidant capacity, and production of reactive oxygen species (ROS) at 6, 12, 18, and 24 h post-hatching. There was a decrease in glucose concentration in the LA-treated animals, and a decrease in ammonia production was observed in the 0.5 µM LA treatment. ETS activity was positively regulated by the addition of LA, with the most significant effects at concentrations of 5.0 and 10.0 µM at 12 and 24 h. For ETS activity, treatments with LA presented the highest values at 24 h, a period when ROS production decreased significantly, for the treatment with 10.0 µM. LA showed positive regulation of energy metabolism together with a decrease in ROS and TAN excretion.